IDENTIFIKASI DAN PENYELESAIAN MASALAH PADA UKM MEUBEL - WILLIAM, . (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
SME business is a business sector which plays an important role in economic development in Indonesia. Existence and role of SMEs which in 2007 reached 49.84 million units, and is 99.99% of the national business, in the order of the national economy is no doubt, by looking at the contribution to employment, the establishment of the Gross Domestic Product (GDP ) national, the value of national exports, and national investment. Furniture in particular SMEs in recent years due to business processes furniture experienced a significant increase, especially in East Java. Constraints that commonly arise in the SME Furniture is usually associated with the scheduling and production costs, which consist of: raw material costs, labor costs, and overhead costs. It is therefore necessary repairs in a manner/method as a solution to the completion of the constraints that typically occurs in the production process in SMEs Furniture.